2006
DOI: 10.1021/ac061476p
|View full text |Cite
|
Sign up to set email alerts
|

Porous SiO2Interferometric Biosensor for Quantitative Determination of Protein Interactions:  Binding of Protein A to Immunoglobulins Derived from Different Species

Abstract: Determination of kinetic and thermodynamic protein binding constants using interferometry from a porous Si Fabry-Perot layer is presented. A protein A capture probe is adsorbed within the pores of an oxidized porous Si matrix, and binding of immunoglobulin G (IgG) antibodies derived from different species is investigated. The relative protein A/IgG binding affinity is human > rabbit > goat, in agreement with literature values. The equilibrium binding constant (K a ) for human IgG binding to surface-immobilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 63 publications
5
110
0
Order By: Relevance
“…The advantage of such sensors include their increased portability and their potential use as implants [31][32][33] . Several investigators have demonstrated nanowire and nanotube devices for high-performance chemical and biomolecular sensing 26,[34][35][36][37][38][39][40] .Multiple-nanowire/tube films were especially sensitive owing to the cumulative response of the wires as well as the lownoise profile resulting from multidevice averaging 35,36 . For sensing purposes, SNAP nanowires have several advantages.…”
Section: Flexible Nanowire Vapour Sensorsmentioning
confidence: 99%
“…The advantage of such sensors include their increased portability and their potential use as implants [31][32][33] . Several investigators have demonstrated nanowire and nanotube devices for high-performance chemical and biomolecular sensing 26,[34][35][36][37][38][39][40] .Multiple-nanowire/tube films were especially sensitive owing to the cumulative response of the wires as well as the lownoise profile resulting from multidevice averaging 35,36 . For sensing purposes, SNAP nanowires have several advantages.…”
Section: Flexible Nanowire Vapour Sensorsmentioning
confidence: 99%
“…5. At the appropriate pH, porous SiO 2 spontaneously adsorbs positively charged proteins such as serum albumin [130,131], fibrinogen [132], protein A [70,114,133], immunoglobulin G (IgG) [134], or horseradish peroxidase [25], concentrating them in the process. For example, a 0.125 mg/mL solution of the monoclonal antibody bevacizumab (trade name Avastin, an anti-cancer drug) spontaneously concentrates in suitably prepared porous SiO 2 by a factor of >100 (unpublished results).…”
Section: Concentrating a Payload By Spontaneous Adsorptionmentioning
confidence: 99%
“…Porous SiO 2 (oxidized porous Si) has a negative surface charge; molecules with positive charges will spontaneously adsorb to the inner pore walls and surface. This method is commonly used to load proteins [70,114,130,[132][133][134] Fabrication of a nanostructured composite from a porous Si template. A variety of solution-or melt-processible organic and biopolymers can be solution-cast or injection-molded into a porous Si or porous SiO 2 host.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…The application of these devices in the biosensors field (Schmitt et al, 2007;Schwartz et al, 2006) is a rapidly developing field due to the possibility of the implementation of real time measurements without the need for more complex and indirect procedures (Marques et al, 2009). A prototype device for refractive index measurement with high sensitivity and high dynamic range based on a Mach-Zehnder integrated interferometer was developed, Fig.…”
Section: Integrated Refractive Index Sensor Based On a Mach-zehnder Imentioning
confidence: 99%